Address to the National Press Club, Washington, D.C., March 25, 1998 - Wolfensohn, James D. (2017)
James D. Wolfensohn, President of the World Bank Group discussed the financial crisis in Asia which began with the emergence of the Thailand crisis. The history of Asian economic and social development has been one of enormous achievement. Since 1975 the number of people living in poverty has been reduced from 700 million to 340 million (roughly 20 percent of the population)—no small achievement. Generally, the region has had strong economic growth. Life expectancy has gone up significantly, while infant mortality has gone down significantly. Primary school enrollment approaches 100 percent. Fiscal management has been remarkable. What changed? We have a crisis now caused by private sector excesses, and to a degree government inaction in the area of supervision. The Bank is focusing on two things: reformation of the financial system, in terms of trying to get the regulation and control that is now being demanded by the Asian authorities themselves; and the impact on the people. Wolfensohn fielded a number of questions from the audience.